Management Transformation and Character Building Through Prophetic Leadership at Al-Mardliyah Islamic Boarding School, Jombang - Ach. Saifullah; Prim Masrokan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research investigates the implementation of prophetic leadership model, comprising shiddiq, amanah, tabligh, and fathanah, at Al-Mardliyah Islamic Boarding School in Jombang, and its implications for modern boarding school management and student character development. Through the employment of a qualitative case study methodology, data were procured via a combination of interviews, observational techniques, and documentary analysis. The study's results demonstrate that prophetic values are institutionalized in program planning, participatory implementation, and exemplary supervision, thereby forming an integrated management system. These values are manifested in curriculum development, digital outreach, managerial innovation, and collaboration with external institutions. The application of prophetic leadership has led to a transformation in the students' character, including improved discipline, integrity, communication skills, cultural ethics, and the ability to adapt to changing times. This study concludes that prophetic leadership is a practical, value-based management framework designed to modernize Islamic boarding schools, integrating spirituality and sustainability into their transformation into contemporary educational institutions. Implicitly, this model can be adopted as a strategic approach for other Islamic boarding schools that wish to enhance management quality while developing the holistic character of their students.